Characteristics of adrenocortical carcinoma in South Korea: a registry-based nationwide survey. Issue 6 (June 2020) - Lim, Jung Soo; Lee, Seung-Eun; Kim, Jung Hee; Kim, Jae Hyeon; ,
Abstract : Purpose: To evaluate the clinical characteristics and prognostic factors in patients with adrenocortical carcinoma (ACC) in South Korea. Methods: A nationwide, registry-based survey was conducted to identify pathologically proven ACC at 25 tertiary care centers in South Korea between 2000 and 2014. Cox proportional hazard model and log-rank test were adopted for survival analysis. Results: Two hundred four patients with ACC were identified, with a median follow-up duration of 20 months (IQR 5–52 months). The median age at diagnosis was 51.5 years (IQR 40–65.8 years), and ACC was prevalent in women ( n = 110, 53.9%). Abdominal pain was the most common clinical symptom ( n = 70, 40.2%), and ENSAT stage 2 was most common ( n = 62, 30.4%) at the time of diagnosis. One hundred sixty-nine patients underwent operation, while 17 were treated with other modalities. The remission rate was 48%, and median recurrence-free survival time was 46 months. Estimated 5-year recurrence-free rate was 44.7%. There were more women, large tumor, atypical mitosis, venous invasion, and higher mitotic count in cancer recurrence group. Estimated 5-year overall survival and disease-specific survival rates were 64.5 and 70.6%, respectively. Higher ENSAT stage and advanced pathologic characteristics were risk factors for all-cause mortality of ACC. Large tumor size and cortisol-secreting tumor were additional risk factors for ACC-specific death. Conclusions: We report the first epidemiologic study regarding ACC in an Asian population. ENSAT stage 4; lymph node involvement; non-operative group; and invasion of vein, sinusoid, or capsule were associated with an increased risk for all-cause mortality.